Computational Fluid Dynamics (CFD) Analyses of Energy and Exergy in Thin Layer Drying of Okra (Abelmoschus esculentus) Slices using Centre Shaft Rotary Tray Cabinet (CSRTC) Dryer - Oyeniyi, S. K.; Olatunbosun, O. S.; Aremu, A. K.; Aviara, N. A.; Iyilade, I. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper presents a simulation of the drying process of okra (Abelmoschus esculentus) in a Center Shaft (CS) Rotary Tray Cabinet Dryer using three drying temperatures (50, 60 and 70 °C). ANSYS 14.5 Workbench was used to simulate the dryer model in 2D (2 Dimensional). The detail of the CFD simulation was utilized to investigate the energy and exergy of the dryer. The ANSYS Design Modeler was used to model the 2D representation of the dryer and the meshing was done using ANSYS ICEM. ANSYS Fluent CFD solver was then used to calculate the alternative using the normal turbulence-realizable k-epsilon model in a steady-state system with improved wall temperature treatment. The simulation outcome was used in calculating the dryer’s exergy and energy analysis based on the thermal efficiency. It was noted that the simulated temperature from the experiment is greater than that of the experiment. The results indicated that the experimental energy utilization (EU), energy utilization ratio (EUR) and energy efficiency increased from 14.1 to 57.93 J/s, 0.15 to 0.20 and 18.89 to 33.98 percent, while the simulated energy utilization ratio increased from 23.91 to 57.68 J/s, 0.19 to 0.20 and 26.21 to 33.40 percent, respectively, and as the drying air temperature increased from 50 °C to 70 °C. Experimental exergy inflow, outflow, exergy loss and exergy efficiency increased from 4.01 J/s to 6.98 J/s, 1.83 J/s to 1.9 J/s, 3.18 J/s to 5.07 J/s and 21 to 27%, while simulated air temperatures increased from 5.01 J/s to 7.49 J/s, 1.33 J/s to 2.20 J/s, 3.66 J/s to 5.29 J/s and 27 to 29% respectively with respect to the drying air temperature range (50–70 °C). Model equations were derived from the plotted graphs to express the energy and exergy parameters as a function of drying temperature.